2005
DOI: 10.1111/j.1467-9701.2005.00715.x
|View full text |Cite
|
Sign up to set email alerts
|

Who Supports Free Trade in Latin America?

Abstract: This paper examines individual trade policy preferences across 17 countries in Latin America. The focus is on whether skilled or unskilled workers are more likely to support liberalised trade and on whether country characteristics, such as factor endowments, alter the preferences of skilled and unskilled workers. Based on the standard Heckscher‐Ohlin model and the Stolper‐Samuelson theorem, wage inequality in developing countries will decrease under free trade and unskilled workers will benefit. We find that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 20 publications
0
24
0
1
Order By: Relevance
“…Bottom‐up preference models assume that there are distributive consequences of trade policy and the public votes based on their perception of how it will affect them, their family, or, more broadly, their country (Balistreri ; Scheve and Slaughter ; Beaulieu et al. ; Mayda and Rodrik ). Standard arguments about the role of economic interests in determining trade policy preferences tend to draw on the Heckscher–Ohlin (HO) theorem and its related Stolper–Samuelson (SS) one (Scheve and Slaughter ; Beaulieu et al.…”
Section: Theories About Trade Preferences: Bottom‐up and Top‐downmentioning
confidence: 99%
See 2 more Smart Citations
“…Bottom‐up preference models assume that there are distributive consequences of trade policy and the public votes based on their perception of how it will affect them, their family, or, more broadly, their country (Balistreri ; Scheve and Slaughter ; Beaulieu et al. ; Mayda and Rodrik ). Standard arguments about the role of economic interests in determining trade policy preferences tend to draw on the Heckscher–Ohlin (HO) theorem and its related Stolper–Samuelson (SS) one (Scheve and Slaughter ; Beaulieu et al.…”
Section: Theories About Trade Preferences: Bottom‐up and Top‐downmentioning
confidence: 99%
“…Standard arguments about the role of economic interests in determining trade policy preferences tend to draw on the Heckscher–Ohlin (HO) theorem and its related Stolper–Samuelson (SS) one (Scheve and Slaughter ; Beaulieu et al. ). The theorems suggest that owners of relatively scarce factors lose from trade liberalization, whereas owners of abundant factors gain.…”
Section: Theories About Trade Preferences: Bottom‐up and Top‐downmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the Stolper-Samuelson theorem does not explain who will benefit from trade among China, Malaysia, and Thailand that are all upper-middleincome economies (World Bank Country and Lending Groups n.d.). Besides, unlike what is expected by the theorem, some studies have shown that, despite the cross-national differences in the distribution of factor endowments, highskilled workers are more likely to support free trade with other countries than low-skilled workers, even in low-skilled labor-abundant countries (Baker 2005;Beaulieu et al 2005).…”
Section: Trade Between China and Its Neighbors And Its Dis-tributive mentioning
confidence: 82%
“…There are some exceptions, as businesses that are less competitive internationally, such as the US steel and textile industries, have repeatedly tried to seek protection from the government. In addition, skilled workers are more likely to support liberalised trade than unskilled workers (Beaulieu et al , 2005).…”
Section: Introductionmentioning
confidence: 99%